Penyuluhan Perilaku Hidup Bersih dan Sehat di Kecamatan Minasatene Kabupaten Pangkajene Kepulauan - Susanti, Rini; Imran, Ali; Briliannita, Anjar; Akbar, Akbar; Yermi, Yermi; B, Muslimin; Pannyiwi, Rahmat; Rasyid, Djusmadi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Clean and healthy living behavior is a behavior that is practiced by students, teachers and the school community on the basis of awareness as a result of learning, so that independently they are able to prevent disease, improve their health, and play an active role in creating a healthy environment. Early learning given at school age helps in instilling awareness of the importance of cleanliness as an effort to maintain health. School-age children are a critical age group, because at that age a child is vulnerable to health problems. In addition to being vulnerable to health problems, school-age children are also in a condition that is very sensitive to stimuli so that they are easily guided, directed and instilled good habits, including clean and healthy living habits. Community service activities in Biraengng Village, Minasatene District, Pangkep Regency were carried out well in one meeting, namely on May 16 2023 which was attended by around 35 participants. Participants in this service are school-age children. This PKM aims to provide information for students about PHBS at SD Negeri Pangkep. The implementation method is carried out with counseling and simulations on how to wash hands and brush your teeth properly. PHBS counseling for school children at Pangkep Public Elementary School ran smoothly, all participants were very enthusiastic about participating in this PKM activity.